Dance Learning Planning with Model Project-Based Learning on the Independent Curriculum at SMAN 1 Cisarua - dewi Shintawati; Heni Komalasari (Universitas Pendidikan Indonesia, 2023)
Freedom to Learn is a new policy program from the Ministry of Education and Culture of the Republic of Indonesia from 2022 to 2024. The Ministry of Education, Culture, Research and Technology (Kemendikbudristek) provides three curriculum options that will be applied to educational units in learning, including 3 curricula, namely the 2013 curriculum, emergency curriculum, and prototype curriculum. This research aims to provide an overview of data and information regarding the results of learning planning using the PJBL model in the independent curriculum. The qualitative research paradigm used a research sample of 2 educators and 37 participants using descriptive qualitative research methods, researchers conducted research using a case study approach. Data collection techniques using questionnaires and interviews, from empirical experience. The results of the learning planning process based on the Independent Learning concept are very effective and flexible if implemented well, and students are required to be more active and innovative in processing their knowledge. This is its unique value so that the teacher's role is not only as an informant. However, it is more of a facilitator and motivator in learning. Curriculum developments in each era reveal changes in behavior and competencies to be achieved, such as balanced competencies between attitudes, skills and knowledge. This article concludes how to implement dance learning using the independent curriculum in Arts, Culture and Skills (SBK) subjects.